NATURAL LEARNING AND MANAGERIAL ACTION: A PHENOMENOLOGICAL STUDY IN THE FIELD SETTING - Burgoyne, J. G.; Hodgson, V. E. (Journal of Management Studies, 1983)
ABSTRACTAn approach to collecting data about managers’ experience of their work is described, involving having them ‘think aloud’ while doing their work, and ‘re‐live’ episodes soon afterwards. Some of the epistemological and methodological issues relating to this research approach are discussed.Examples of data are given, and 37 episodes of managerial work are analyzed for evidence relating to the question of how managers learn naturally from everyday experience.The analysis suggests that the concept of levels of learning proposed by Bateson (1973) is useful. An initial categorization of processes of learning, arising from the data, are presented. Some evidence that the profounder forms of learning are incremental rather than sudden is presented, and the issue of the functionality of profounder versus more superficial forms of learning in relation to everyday managerial work is raised.